1978
DOI: 10.1159/000232067
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of IgG4 in Discordant Correlations between Intracutaneous Skin Tests and RAST

Abstract: Comparison of intracutaneous skin tests and RAST in 2 groups of patients, one consisting of 16 individuals having multiple allergies to pollen, mold and animal dander and the other of 10 patients allergic to mold only, revealed that skin tests were more sensitive than RAST. Skin reactions of 3+ to 4+ were frequently associated with negative RAST results. This was observed more so in mold-allergic patients. In a few cases (6%) RAST showed 2+ reactions while the skin tests were negative. Leukocytes from allergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…Vijay et al [8] suggest that cell-bound IgG4 is a functional component of some im mediate hypersensitivity reactions. The dis appearance of the sensitizing capacity of the sera, after they had been heated for 2 h at 56 °C ( fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vijay et al [8] suggest that cell-bound IgG4 is a functional component of some im mediate hypersensitivity reactions. The dis appearance of the sensitizing capacity of the sera, after they had been heated for 2 h at 56 °C ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…Vijay and Perelmutter [7] observed PCA inhibition in mon keys by IgG4-myeloma protein; they also described histamine release from human leukocytes, mediated by the IgG4 subclass. The same authors [8] suggested that skintest reactivity may be due to the presence of IgG4 reagins in some patients.…”
Section: Introductionmentioning
confidence: 96%
“…IgG4 has been suggested to have homocytotropic properties (120,121) but these results have not been confirmed by us (95) or others (115,116).…”
Section: Rationales For Utilization Of Igg-allergen Complexesmentioning
confidence: 73%
“…Similar correla tion was reported previously by Lichten stein et al [12] between allergens-and anti-IgE-induced histamine release in ragweed-sensitive donors. On the other hand, recent data indicate the presence of Fc re ceptors for human IgG on basophils [13] and liberation of histamine from basophils not only by anti-IgG [3,12] but also by anti-IgG4 [14,15]. Contamination of the anti-IgG4 preparations used in this series of experiments by anti-IgE, anti-light chain, and/or anti-Fab was excluded by the careful specificity assessment using radioimmunoas says [6] and by passive sensitization experi ments [5], The fact that anti-IgG4 can degranulate human basophils [4,5] and the correlation between allergens-and anti-IgG4-induced degranulation, as well as the correlation between anti-IgE-and anti-IgG4-mediated degranulation [5], strong ly suggest that IgG4 subclass to be a func tional component of immediate hypersensi tivity.…”
Section: Discussionmentioning
confidence: 99%